1998
DOI: 10.1051/rnd:19980105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding sugar beet fibre and wheat bran to a starch diet on the absorption kinetics of glucose, amino-nitrogen and volatile fatty acids in the pig

Abstract: -The purpose of this study with the pig was to analyse the influence of the type of dietary fibre on quantitative kinetics of the absorption of nutrients deriving from enzymatic digestion in the small intestine and that of volatile fatty acids (VFA) deriving from microbial digestion in the hindgut influenced by the length of adaptation to the diet. Two groups of four pigs were fitted with a device for measuring absorption by simultaneous analysis of the differences in the porto-arterial concentrations of nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Anderson (1974) demonstrated that the insulin and glucose response to high-fiber diets can depend upon the properties of the starch in the diet. Michel and Rérat (1998) noted that glucose absorption was only slightly modified by the type of fiber, i.e., wheat bran or sugar beet pulp, added to the diet of growing pigs.…”
Section: Insulin Glucose and Ffamentioning
confidence: 99%
“…Anderson (1974) demonstrated that the insulin and glucose response to high-fiber diets can depend upon the properties of the starch in the diet. Michel and Rérat (1998) noted that glucose absorption was only slightly modified by the type of fiber, i.e., wheat bran or sugar beet pulp, added to the diet of growing pigs.…”
Section: Insulin Glucose and Ffamentioning
confidence: 99%
“…Volatile fatty acids are the main products of the digestive flora in the large bowel, allowing a large recovery of energy from nutrients poorly broken down in the small intestine. From several experiments with different energetic [67,128,160,168], it was possible to show that the production and absorption of volatile fatty acids increased more or less with the crude fibre content of the feed, according to its nature, and with the presence of some indigestible carbohydrates such as lactose or sorbitol in the diet. Contrasting with the early energy absorption derived from enzymic degradation, energy absorption under the form of volatile fatty acids occurred later, thus making it possible to partially bridge the energy gap during the interprandial period [145].…”
Section: Respective Roles Of Enzymatic and Microbial Hydrolysis In DImentioning
confidence: 99%
“…Soluble dietary fibre, such as guar gum, significantly decreased glucose absorption in the small intestine of pigs (Rainbird et al, 1984), markedly reduced the peak postprandial plasma glucose and insulin concentrations (Heppell, 1985;Sambrook and Rainbird, 1985), and lowered the plasma cholesterol level in rats (Overton et al, 1994). On the other hand, in pigs fed diets with sugar beet fibre and wheat bran, no effect on glucose concentration in portal and arterial blood was observed (Michel and Rerat, 1998).…”
Section: Introductionmentioning
confidence: 99%